Choosing Choices: Agenda Selection With Uncertain Issues. Issue 1 (24th January 2013) - Godefroy, Raphael; Perez‐Richet, Eduardo
Abstract : We study selection rules: voting procedures used by committees to choose whether to place an issue on their agenda. At the selection stage of the model, committee members are uncertain about their final preferences. They only have some private information about these preferences. We show that voters become more conservative when the selection rule itself becomes more conservative. The decision rule has the opposite effect. We compare these voting procedures to the designation of an agenda setter among the committee and to a utilitarian social planner with all the ex interim private information.